BOOSTING LOCAL SKINCARE SALES: THE POWER OF CONTENT MARKETING, INFLUENCERS, AND ELECTRONIC WORD OF MOUTH (E-WOM) - Salsabila, Audrey Safa; Wibowo, Setyo Ferry; Monoarfa, Terrylina Arvinta (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study examines the influence of content marketing, influencer endorsement, and electronic word of mouth on purchase intention of local skincare products among Generation Z in Jabodetabek. In the digital era, the rapid development of information and communication technology has changed business and marketing strategies, creating new opportunities and challenges. This study involved 250 respondents who were active users of the TikTok social media platform and had been exposed to local skincare product marketing content. Data analysis was conducted using the Structural Equation Model (SEM) method. The results showed that content marketing and electronic word of mouth had a positive and significant effect on purchase intention, while influencer endorsement had no significant effect. These findings highlight the importance of an effective digital marketing strategy in attracting consumer interest and providing insight for companies in developing more adaptive and innovative marketing strategies amidst increasingly fierce competition.